Prevalence and correlates of substance use among trans*female youth ages 16–24 years in the San Francisco Bay Area. (1st February 2015) - Rowe, Chris; Santos, Glenn-Milo; McFarland, Willi; Wilson, Erin C.
Highlights: Substance use was highly prevalent among trans*female youth. Psychosocial risk factors were associated with increased odds of substance use. Understanding these psychosocial mechanisms can inform substance use interventions. Targeting substance use represents a possible avenue to mitigate health disparities. Abstract: Background: Substance use is highly prevalent among transgender (trans*) females and has been associated with negative health outcomes, including HIV infection. Little is known about psychosocial risk factors that may influence the onset of substance use among trans*female youth, which can contribute to health disparities during adulthood. Methods: We conducted a secondary data analysis of a study on HIV risk and resilience among trans*female youth ( N = 292). Prevalence of substance use was assessed and multivariable logistic regression models were used to examine the relationship between posttraumatic stress disorder (PTSD), psychological distress, gender-related discrimination, parental drug or alcohol problems (PDAP) and multiple substance use outcomes. Results: Most (69%) of the trans*female youth reported recent drug use. In multivariable analyses, those with PTSD had increased odds of drug use [AOR = 1.94 (95% CI = 1.09–3.44)]. Those who experienced gender-related discrimination had increased odds of drug use [AOR = 2.28 (95% CI = 1.17–4.44)], drug use concurrent with sex [AOR = 2.35 (95% CI = 1.11–4.98)] and use of multiple drugs [AOR = 3.24 (95% CI = 1.52–6.88)]. Those with psychological distress had increased odds of using multiple heavy drugs [AOR = 2.27 (95% CI = 1.01–5.12)]. Those with PDAP had increased odds of drugs use [AOR = 2.62 (95% CI = 1.43–4.82)], drug use concurrent with sex [AOR = 2.01 (95% CI, 1.15–3.51)] and use of multiple drugs [AOR = 2.10 (95% CI = 1.22–3.62)]. Conclusions: Substance use is highly prevalent among trans*female youth and was significantly associated with psychosocial risk factors. In order to effectively address substance use among trans*female youth, efforts must address coping related to gender-based discrimination and trauma. Furthermore, structural level interventions aiming to reduce stigma and gender-identity discrimination might also be effective.